YouTube English Channel as a learning medium: Its effect on students’ speaking skills of Islamic senior high school - Faurina Anastasia; M. Riskiyadi Siregar; Najiyah Jasmin; M. Mukhlis; Nur Aliyah (Englisia: Journal of Language, Education, and Humanities, 2026)
This study addresses a persistent challenge in English language instruction: although speaking proficiency is a core competency, many learners face barriers such as low self-confidence, limited access to varied learning media, and inadequate opportunities for active practice. The present research investigates the effect of using a YouTube-based English Channel as a learning medium on the speaking skills of students at an Islamic Senior High School. A quasi-experimental design was employed, involving two intact classes: XI MIA 1 (experimental group), which received instruction using a YouTube English Channel, and XI MIA 4 (control group), which was taught without the use of this medium. Speaking performance was assessed through video-recorded tests measuring five sub-skills: pronunciation, grammar, vocabulary, fluency, and comprehension. The experimental group demonstrated a mean gain of 5.71 points (from 67.26 to 73.03), whereas the control group showed only a marginal increase of 0.94 points (from 68.72 to 69.56). These results indicate that the integration of the YouTube English Channel yielded substantially greater improvement in speaking skills compared to conventional instruction. The study concludes that YouTube-based media contribute to a more contextualized, engaging, and interactive learning environment, thereby facilitating more optimal development of students’ oral proficiency. Pedagogically, the findings support the integration of digital media into English language teaching. Future research is encouraged to extend the contextual scope, include more diverse participant samples, and examine additional affective variables such as learner motivation and self-confidence.